Retakaful operation in Malaysian practice: issues and solutions - Nan Noorhidayu bt Megat Laksana (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
Retakāful is an important financial tool through which takāful operators pay an agreed amount from takāful fund to the retakāful operators in order to get protection against loss or unexpected risk. Retakāful is an alternative for takāful operators to reinsure their risk. Some of the concepts and practices in reinsurance are relevant and acceptable in the practice of retakāful. This study attempts to discuss and examine retakāful operation as implemented by retakāful operators in Malaysia. Three retakāful operators in Malaysia had been selected by the researcher in order to get a clearer understanding of the implementation of retakāful operation models which are ACR Retakāful SEA Berhad, MNRB Retakāful Berhad and Munich Re Retakāful Berhad. In addition, this study attempts to analyse the fiqhī issues in retakāful operation. The issues can be divided into two types; general fiqhī and specific fiqhī. For general fiqhī issues, some issues have been raised by the researcher regarding the permissibility of takāful operators reinsuring with conventional reinsurance, the Muslim scholar's opinion on retakāful operators who take the risk from conventional insurance and retrocession issues. For the specific fiqhī issues, the issue of excess of loss in facultative and treaty have been examined. This study used two methods of data collection; library research and interviews with experts at three retakāful operators in Malaysia. This study has concluded with a number of findings. Most of the SharÊÑah advisors of these three retakāful operators agreed that there is no SharÊÑah issues in excess of loss treaties. However, only a minority said there are SharÊÑah issues in excess of loss treaties. The SharÊÑah issues may be seen at the takāful operational level but not at the retakāful operational level. Additionally, this study finds that the working experience of SharÊÑah advisors and SharÊÑah officers of the three retakāful operators in Malaysia is less than 10 years. This shows that retakāful operators in Malaysia still lack working experience and do not have many experts to oversee the industry.